Plants Nutrition and Growth Stimulation with the Help of Nanotechnologies - I. Churilov, G.; G. Churilov, D.; G. Churilov, S.; N. Borychev, S.; V. Byshov, N.; V. Churilova, V.; D. Polischuk, S. (International Journal of Engineering and Technology, 2018)
The consistent use of some branches of agrochemical science in crop growing is in the concept of a comprehensive system approach we propose to the issue of plants nutrition and growth stimulation with the help of nanobiopreparations based on copper and cobalt nanopowders. We propose to optimize the technology of a number of agrochemical measures, and more precisely, to reduce them to a single pretreatment of seeds with a preparation containing necessary trace elements in the nano form.This article presents toxic and stimulating effects of using nanoparticles in agro and biotechnology. The developed bio preparations, based on nanoparticles of metal-trace elements (iron, cobalt, copper), have a number of advantages over existing analogues and they are as it follows:â€¢ multifunctional action;â€¢ low consumption rates of preparations up to 1.0 g per hectare seeding rate, while pre-sowing treatment can be combined with dressing, which does not require additional energy costs;â€¢ a comparative assessment of the toxicity of nanopreparations compared with salts of trace elements (iron and copper sulphates, cobalt chloride) proves that salts are 8-10 times more toxic than nanopreparations;â€¢ low cost of nanopreparations (NP) compared with the cost of an equivalent dose of traditional mineral micro fertilizers and drugs to prevent plant diseases;â€¢ ecological safety.The uniqueness of the proposed technology lies in the fact that its use in agriculture does not require any special equipment or an increase in the staff of the enterprise. In the process of applying the proposed preparations, the natural processes of agrobiocenosis are not disturbed and soil fertility is preserved.The effect of nanobiopreparations on living organisms and the effect of â€œlow dosesâ€ compared to substances in the usual physical-chemical state, make possible to obtain scientifically based and objective results of the effect of nanoparticles on plants nutrition and growth stimulation.Â Â